Knowledge Level of Health Care Providers about Complicated Grief during the COVID-19 Pandemic - Sareh Dashti; Tahereh Fathi Najafi; Fatemeh Mohammadzadeh; Afsaneh Rezaei Kalat; Narjes Bahri (Iranian Journal of Psychiatry, 2022)
Objective: The coronavirus 2019 (COVID -19) pandemic had great psychological impact on COVID-19 patients and their families. Relatives of the deceased COVID-19 patients are at risk for complicated grief. Healthcare providers (HCPs) should be able to identify complicated grief cases. The aim of this study was to assess HCP knowledge regarding complicated grief during the COVID-19 pandemic.